Supervisi Akademik Kepala Madrasah dalam Peningkatan Kinerja Guru Menghadapi Era Society 5.0 - Zulhijjah Zulhijjah (Departement of Mathematics Education, 2024)
This research aims to identify the patterns of planning, implementation, evaluation, and follow-up in academic supervision by the headmaster to improve teacher performance at MAN 4 East Aceh in facing Society 5.0 era, as well as to explore the constraints faced. The research used a qualitative approach. The results show that academic supervision at MAN 4 East Aceh is carried out systematically through stages of planning, implementation, evaluation, and follow-up. Planning includes developing a supervisory program, assigning tasks to supervisor teams, and creating a supervisory schedule while implementation is done through classroom visits and observations. Evaluation involves assessing learning tools and teaching practices with feedback and continuous coaching as follow-ups. Constraints include scheduling delays; limited human resources; slow technology adaptation; and infrastructure limitations. The practical implications of this study indicate the need for technology training for teachers and investment in infrastructure facilities. Theoretical implications strengthen the importance of comprehensive and adaptive supervision approaches in facing Society 5.0 era. However, this study is limited among others so its results may not be fully generalizable.Recommendations for future research involve expanding studies to other madrasahs use mixed methods for more comprehensive analysis.